Evolution of the Indian economy; Textbook in economics for class XI - "Gill, K S" (New Delhi, 1985)
This book, first published in December 1977, has since been reprinted five times. There have been several reprints of its Hindi edition. An Urdu version of the book has also been published. A thorough revision of the book had become necessary to incorporate developments in the Indian economy since 1977, update the data, and adjust the contents to the revised syllabus for Class XI adopted bu the NCERT in January 1984.
Keywords: Economics